PENGALAMAN PIMPINAN RUANG DALAM MELAKUKAN SUPERVISI PELAKSANAAN PEMBERIAN CAIRAN INTRAVENA - ana zakiyah (Akademi Kebidanan Griya Husada Surabaya, 2016)
ABSTRACTThe nurse has responsibility in managing the administration of intravenous fluids. Efforts made by space leaders to evaluate the implementation of these actions through supervision activities so as to produce quality services. This study aims to obtain an overview of the meaning and meaning of supervision of the implementation of intravenous fluids carried out by the space manager. The research design used was descriptive phenomenology method, data collection with FGD and in-depth interviews. Participants in this study were taken by purposive sampling and data analysis using the Collaizi method. The results of the study identified 5 themes, namely the understanding of the leadership of the room about supervision, maintaining performance, increasing knowledge and skills, spatial leadership providing support and encouragement, less standardized supervision. Based on the results of the research obtained, space leaders need to understand, carry out management functions to support the smooth functioning of inpatient services that are their responsibility, especially in supervision activities that can be carried out in stages and continuously.